Comparison of Fetomaternal Outcomes between Scarred and Unscarred Uterus in Placenta Previa Cases - Abdullah, Sana (Indus Journal of Bioscience Research, 2025)
Background: Placenta previa remains a significant obstetric challenge, especially when compounded by a history of uterine scarring such as prior cesarean sections. A scarred uterus is increasingly recognized for its association with abnormal placentation, increased surgical complexity, and adverse fetal outcomes. With rising cesarean rates globally, understanding the comparative risks posed by scarred versus unscarred uteri in placenta previa is essential for optimizing clinical management and maternal-neonatal safety. Objective: To compare fetomaternal outcomes between scarred and unscarred uteri among women diagnosed with placenta previa. Methodology: This descriptive case series was conducted in the Department of Obstetrics and Gynaecology, Shalamar Hospital, Lahore, Pakistan, from November 2024 to April 2025. A total of 176 pregnant women (88 with scarred uteri and 88 with unscarred uteri) diagnosed with placenta previa beyond 28 weeks gestation was included using non-probability purposive sampling. Data were collected through structured proformas and analyzed using SPSS version 22. Results: Women with scarred uteri had significantly higher rates of postpartum hemorrhage (68.2% vs. 40.9%; p